2011
DOI: 10.1016/j.jprot.2011.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of proteomics of Leishmania spp. to the understanding of differentiation, drug resistance mechanisms, vaccine and drug development

Abstract: :Leishmania spp., protozoan parasites with a digenetic life cycle, cause a spectrum of diseases in humans. Recently several Leishmania spp. have been sequenced which significantly boosted the number and quality of proteomic studies conducted. Here a historic review will summarize work of the pre-genomic era and then focus on studies after genome information became available. Firstly works comparing the different life cycle stages, in order to identify stage specific proteins, will be discussed. Identifying of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
5

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 71 publications
0
25
0
5
Order By: Relevance
“…Proteomics partially overcomes this hurdle: it has been extensively employed to decipher mechanisms of drug resistance [47][48][49], but this still overlooks some metabolic subtleties that are inherent to the complexity of the intracellular environment. A metabolome database for Leishmania has been developed [50], and a number comprehensive reviews have been published [51][52][53].…”
Section: Introductionmentioning
confidence: 99%
“…Proteomics partially overcomes this hurdle: it has been extensively employed to decipher mechanisms of drug resistance [47][48][49], but this still overlooks some metabolic subtleties that are inherent to the complexity of the intracellular environment. A metabolome database for Leishmania has been developed [50], and a number comprehensive reviews have been published [51][52][53].…”
Section: Introductionmentioning
confidence: 99%
“…Although the molecules excreted and secreted by Leishmania spp. have been a target of interest for decades and have been identified as potential candidates for vaccines, 32 they have not been extensively explored for the diagnosis of leishmaniasis. 5,6,12,13,15 In this report, we present new data suggesting that ESAs isolated from three different species of Leishmania (from the most prevalent species in the Americas) L.…”
Section: Discussionmentioning
confidence: 99%
“…Essentially, it has been observed that most of the regulation in Leishmania is obtained posttranslationally. Hence proteomic studies provide more knowledge about differences between resistant and sensitive parasites as compared to genomic data [58]. It is a good indicator about protein abundance and expression and can yield an insight into species differences, stage differentiation, drug resistance, and virulence [59].…”
Section: Concluding Remarks and Future Prospectsmentioning
confidence: 99%
“…However, on the downside, a number of differentially expressed proteins found after proteome comparison lack an annotated function [57]. Most of the gel-based proteome comparisons only highlight abundant proteins, whereas the not-so-abundant ones seem to be masked [58]. Hence further research needs to be done in characterizing unidentified proteins, not-so-abundant proteins, and proteins with unknown functions.…”
Section: Concluding Remarks and Future Prospectsmentioning
confidence: 99%